2004
DOI: 10.1177/0007650304263047
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Attractiveness and Corporate Social Orientation: Do Our Values Influence Our Preference for Affirmative Action and Managing Diversity?

Abstract: This study examines the impact of corporate social orientation on organizational attractiveness as it relates to information about an organization’s handling of diversity issues. Using Aupperle’s notion of corporate social orientation (CSO), we examined how CSO affects perceived attractiveness of organizations’ emphasizing affirmative action versus diversity management policies in their recruitment literature. Respondents to a survey of 343 college students reported a more favorable assessment of affirmative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 62 publications
5
56
1
2
Order By: Relevance
“…A considerable number of studies support the presence of a relationship between CSR and employer attractiveness (Backhaus, Stone, & Heiner, 2002;Evans & Davis, 2011;Greening & Turban, 2000;Joo et al, 2016;Lis, 2012;Smith, Wokutch, Harrington, & Dennis, 2004;Turban & Greening, 1996;Zaid & Al-Manasra, 2013). At the other extreme end, substantial research findings indicate that CSR is relatively unimportant as an attractive element of organizations, where other traditional job elements like salary and promotional opportunities are more essential (Bergen, 2008;Maheshwari & Yadav, 2015;Pingle & Sharma, 2013;Ramasamy et al, 2008;Sohn, Sohn, KlassWissing, & Hirsch, 2015;Verma & Ahmad, 2016).…”
Section: The Relationship Between Csr and Employer Attractivenessmentioning
confidence: 99%
“…A considerable number of studies support the presence of a relationship between CSR and employer attractiveness (Backhaus, Stone, & Heiner, 2002;Evans & Davis, 2011;Greening & Turban, 2000;Joo et al, 2016;Lis, 2012;Smith, Wokutch, Harrington, & Dennis, 2004;Turban & Greening, 1996;Zaid & Al-Manasra, 2013). At the other extreme end, substantial research findings indicate that CSR is relatively unimportant as an attractive element of organizations, where other traditional job elements like salary and promotional opportunities are more essential (Bergen, 2008;Maheshwari & Yadav, 2015;Pingle & Sharma, 2013;Ramasamy et al, 2008;Sohn, Sohn, KlassWissing, & Hirsch, 2015;Verma & Ahmad, 2016).…”
Section: The Relationship Between Csr and Employer Attractivenessmentioning
confidence: 99%
“…Garriga and Melé (2004) have mapped the terrain of various CSR theories, sorting these into four categories: (1) instrumental 3 It should be noted that, while much of the literature review and policy discussion is from the buyer's perspective (i.e., government and public procurement as CSR drivers), this paper examines supplier CSR orientations in order to assess the buyer's influences on those orientations. 4 See, for example, Acar et al (2001), Aupperle et al (1985), Burton et al (2000), Edmondson and Carroll (1999), Ibrahim and Angelidis (1993, 1994, 1995, Ibrahim and Parsa (2005), Ibrahim et al (1997), Petrick et al (1994), Pinkston and Carroll (1994), Smith and Blackburn (1988), Smith et al (2001Smith et al ( , 2004. The instrument has been well tested for content validity and reliability; see Ibrahim et al (2008, p. 168) on the strength of this methodology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The final instrument has eights items in each component, four items taken respectively from Tan and Komaran (2006) and Aupperle (1984). The original survey, developed by Aupperle (1984), has been widely adopted in the literature, specifically to test the Carroll conceptualisation of CSR (Ibrahim and Angelidis, 1995;Pinkston and Carroll, 1996;Edmondson and Carroll, 1999;Smith et al, 2001Smith et al, , 2004Ibrahim et al, 2003;Marz et al, 2003;Angelidis and Ibrahim, 2004;Ibrahim and Parsa, 2005). The instrument, whose design was guided by the definitions of each of the CSR components, covers all CSR dimensions in the Carroll CSR pyramid construct.…”
Section: Methodsmentioning
confidence: 99%
“…Although philanthropy was viewed as a highly desirable and prized component of CSR, it is seen as being less important than the other three components of CSR (Kakabadse et al, 2005). Many studies have provided empirical evidence on general perception and understanding of CSR based on Carroll's pyramid of CSR framework (Pinkston and Carroll, 1996;Ibrahim et al, 2003;Kusku and Zarkada-Fraser, 2004;Ibrahim and Parsa, 2005;Peterson, 2004;Smith et al, 2004;Smith et al, 2001;Maignan and Ferrell, 2003). Edmondson and Carroll (1999) applied the Aupperle's (1984) forced-choice instrument to black business owners and found that the philanthropic components is weighted higher than previously reported.…”
Section: Csr Frameworkmentioning
confidence: 99%